2017
DOI: 10.1111/ijfs.13405
|View full text |Cite
|
Sign up to set email alerts
|

Superfine grinding improves the bioaccessibility and antioxidant properties of Dendrobium officinale powders

Abstract: In herbal markets, an overwhelming majority the D. officinale are sold in spiral or spring form, and this kind of product would lead to the incomplete release of some nutrients. To increase the bioaccessibility of D. officinale, we report a method of pulverisation treatments including general and superfine grinding to reduce the particle size. In comparison with coarse D. officinale, the superfine ground D. officinale with particle sizes of <18 lm resulted in significant higher bulk density, better flowability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 48 publications
6
35
1
Order By: Relevance
“…The IC 50 values of aqueous extracts from CM and its SS powders decreased with the increase in grinding time, from 1.54 and 2.42 ml/ml to 0.32 and 0.34 ml/ml for 10 hr, respectively. It indicated that the antioxidant activity of CM and SS aqueous extracts increased significantly with the decrease in particle size, which was consistent with the findings of Meng et al (). It was reported that the antioxidant activity of D. officinale powder with the size of <18 μm was higher than that of 37–75, 75–150, and 150–350 μm.…”
Section: Results and Disscusionsupporting
confidence: 91%
“…The IC 50 values of aqueous extracts from CM and its SS powders decreased with the increase in grinding time, from 1.54 and 2.42 ml/ml to 0.32 and 0.34 ml/ml for 10 hr, respectively. It indicated that the antioxidant activity of CM and SS aqueous extracts increased significantly with the decrease in particle size, which was consistent with the findings of Meng et al (). It was reported that the antioxidant activity of D. officinale powder with the size of <18 μm was higher than that of 37–75, 75–150, and 150–350 μm.…”
Section: Results and Disscusionsupporting
confidence: 91%
“…Compared with the span of M60, the span values first decreased (from 2.60 to 2.48) and then increased (from 2.48 to 2.73) as the size of the soybean residue powder decreased. This behavior was inconsistent with the conclusion that there was a smaller value of span in the superfine powder (Huang, Dou, Li, & Wang, ; Zhang, Xu, & Li, ), but it disagreed with results for Dendrobium officinale (Meng et al, ). The differences may have been due to differences in the milling and sieving processes.…”
Section: Resultsmentioning
confidence: 58%
“…In China, there are more than seventy-eight species and two varieties, some of which show bioactivities such as immunomodulatory properties, antitumour activity and antioxidative activity (Xing et al, 2013;Meng et al, 2017). In China, there are more than seventy-eight species and two varieties, some of which show bioactivities such as immunomodulatory properties, antitumour activity and antioxidative activity (Xing et al, 2013;Meng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%